Generation and expression of circadian oscillation in the stingless bee Melipona quadrifasciata (Hymenoptera; Apinae; Meliponini) - Yamashita, Cintia Etsuko (2013)
Daily rhythms of insects are generated by a circadian system localized in the protocerebrum and in the optic lobes of the central nervous system. The circadian system is composed by coupled oscillators connected to input and output pathways. The oscillator generates rhythms by molecular processes, linked in feedback loops. In the input pathways the components are involved in light mediated-transduction. In the output, several neuropeptides are involved. Foragers of the stingless bee Melipona quadrifasciata exhibit a daily activity rhythm. Foragers have been used here to identify circadian components, through three different approaches: I) analysis of gene expression; II) identification of structures in the central nervous system; III) comparative study of neuropeptides possibly related with the circadian system, using Apis mellifera as the reference species. I) Fragments of putative clock genes were cloned. Only period (per) gene showed rhythmic expression, peaked at 1h after lights off. Non statistically significant rhythms were detected in cryptochrome (cry), clock and cycle genes expression. II) Antibodies against PER, CRY (an input pathway protein) and pigment dispersing hormone (an output pathway neuropeptide) evinced several areas in the brain and in the optic lobes. PER and CRY were localized in the optic lobes and in fibers in the protocerebral region, in a rhythmic pattern. PDH was observed in cell bodies in the lateral protocerebrum, in projections in the brain and in some fibers in the optic lobes. III) Neuropeptides probably related to the circadian system, were found in A. mellifera and M. quadrifasciata. Some of them: tachykinin-related peptide, allatostatin, and FMRF-related peptide were rhythmic and present in specie-specific patterns. The circadian system of M. quadrifasciata showed particularities in the putative clock components when compared with A. mellifera and other insects. The expression, localization, distribution and temporal dynamics of the circadian system point out a novel, specific feature